ANALISIS PENGARUH KUALITAS PELAYANAN E- COMMERCE TERHADAP KEPUASAN KONSUMEN SHOPEE PADA MAHASISWA UNIVERSITAS ALMA ATA FAKULTAS EKONOMI DAN BISNIS ANGKATAN 2018 – - Novitasari, Irma (IJMA (Indonesian Journal of Management and Accounting), 2020)
The purpose of this study was to determine the analysis of the effect of the quality of e-commerce services on shopee consumer satisfaction at Alma University students at the Faculty of Economics and Business Class of 2018-2021. This type of research uses quantitative research, data collection methods Non-probability sampling method used is purposive sampling. The population in this study is the active students of Alma Ata University, Faculty of Economics and Business Class of 2018-2021 with a population of 100 respondents. The results of this study have been Validity, Reliability, Data Analysis Techniques with classical assumptions in the form of Normality, Multicollinearity, Heteroscedasticity, and Glejser Tests, Hypothesis Testing with T and F Tests and Multiple Linear Analysis using the Statistical Product and Service Solution (SPSS) program. So that the results obtained are significant relationships between the variables studied, namely based on the value of Fcount > Ftable, which is 13.487 > 3.087. significant F 0.000, then H0 is rejected so that the Effectiveness Variable (X.1), Fulfillment Variable (X2), Reliability Variable (X.3), Privacy Variable (X.4), Responsiveness Variable (X.5), Compensation Variable (X .6), Contact variable (X.7), simultaneously has a positive and significant effect on Consumer Satisfaction (Y). So the hypothesis is that there is a simultaneous effect of the Effectiveness Variable (X.1), Fulfillment Variable (X2), Reliability Variable (X.3), Privacy Variable (X.4), Responsiveness Variable (X.5), Compensation Variable X.6), the Contact variable (X.7), has an effect on the performance of service quality as measured by Consumer Satisfaction (Y) at Alma Ata University Students, Faculty of Economics and Business.